A Study on the Effects of Temperature, Punch Radius and Punch Stroke on Forming Force When Bending SS400 Steel Plate - Vuong, Gia Hai; Nguyen, Thi Hong Minh; Nguyen, Duc Toan (JST: Engineering And Technology For Sustainable Development, 2021)
Sheet metal forming process is a basic deformation method in the mechanical field. In particular, bending deformation processing is a universal processing method which is widely used to form sheet metal parts such as aviation industry, shipbuilding, automotive and so on. During sheet metal bending process, the forming force is a very important output parameter that needs to be determined to ensure the load capacity of a machining equipment. This forming force magnitude will vary according to machining conditions, Geometric shapes of products, sheet materials, etc. This study examines the influence of technological and geometric parameters such as: work-piece temperature, punch speed and sheet thickness to bending force when forming V-shape of SS400 sheet material.